Cortico-cerebellar functional connectivity and sequencing of movements in schizophrenia - Kasparek, Tomas; Rehulova, Jitka; Kerkovsky, Milos; Sprlakova, Andrea; Mechl, Marek; Mikl, Michal (BMC psychiatry, 2012)
BACKGROUND: Abnormal execution of several movements in a sequence is a frequent finding in schizophrenia. Successful performance of such motor acts requires correct integration of cortico-subcortical processes, particularly those related to cerebellar functions. Abnormal connectivity between cortical and cerebellar regions with resulting cognitive dysmetria has been proposed as the core dysfunction behind many signs and symptoms of schizophrenia. The aim of the present study was to assess if these proposed abnormalities in connectivity are a unifying feature of schizophrenia, or, rather, reflect a specific symptom domain of a heterogeneous disease. We predicted that abnormal functional connectivity between the motor cortex and cerebellum would be linked with abnormal performance of movement sequencing. METHODS: We examined 24 schizophrenia patients (SCH) and 24 age-, sex-, and handedness-matched healthy controls (HC) using fMRI during a modified finger-tapping task. The ability to perform movement sequencing was tested using the Neurological Evaluation Scale (NES). The subjects were categorized into two groups, with (SQ+) and without (SQ-) movement sequencing abnormalities, according to the NES-SQ score. The effects of diagnosis and movement sequencing abnormalities on the functional connectivity parameters between the motor cortex and cerebellum (MC-CRBL) and the supplementary motor cortex and cerebellum (SMA-CRBL) activated during the motor task were analyzed. RESULTS: We found no effect of diagnosis on the functional connectivity measures. There was, however, a significant effect on the SQ group: SQ + patients showed a lower level of MC-CRBL connectivity than SQ- patients and healthy controls. Moreover, the level of MC-CRBL and SMA-CRBL negatively correlated with the magnitude of NES-SQ abnormalities, but with no other NES domain. CONCLUSIONS: Abnormal cortico-cerebellar functional connectivity during the execution of a motor task is linked with movement sequencing abnormalities in schizophrenia, but not with the diagnosis of schizophrenia per se. It seems that specific patterns of inter-regional connectivity are linked with corresponding signs and symptoms of clinically heterogeneous conditions such as schizophrenia.
Keywords: Brain Mapping; mapování mozku; Adult; Magnetic Resonance Imaging; nervová síť; pohyb; Fingers; Cerebellum; Motor Cortex; Motor Skills; Neural Pathways; Humans; Schizophrenia; ženské pohlaví; dospělí; magnetická rezonanční tomografie; Female; mužské pohlaví; motorické dovednosti; Male; nervové dráhy; schizofrenie; mozeček; Image Processing, Computer-Assisted; mladiství; lidé středního věku; prsty ruky; Middle Aged; motorické korové centrum; lidé; Adolescent; Movement; Nerve Net; počítačové zpracování obrazu